2010
DOI: 10.5194/hess-14-309-2010
|View full text |Cite
|
Sign up to set email alerts
|

Less rain, more water in ponds: a remote sensing study of the dynamics of surface waters from 1950 to present in pastoral Sahel (Gourma region, Mali)

Abstract: Abstract. Changes in the flooded area of ponds in the Gourma region from 1950 to present are studied by remote sensing, in the general context of the current multi-decennial Sahel drought. The seasonal and interannual variations of the areas covered by surface water are assessed using multidate and multi-sensor satellite images (SPOT, FORMOSAT, LANDSAT-MSS, -TM, and -ETM, CORONA, and MODIS) and aerial photographs (IGN). Water body classification is adapted to each type of spectral resolution, with or without a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 17 publications
(32 reference statements)
0
45
0
4
Order By: Relevance
“…Hydrological responses differed greatly between these two regions. In Sahel, the drought coincided with an observed increase in flow [Leblanc et al, 2008;Mah e and Paturel, 2009;Gardelle et al, 2010]. This paradox has been explained by simultaneous land clearance during extensive agriculture development.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrological responses differed greatly between these two regions. In Sahel, the drought coincided with an observed increase in flow [Leblanc et al, 2008;Mah e and Paturel, 2009;Gardelle et al, 2010]. This paradox has been explained by simultaneous land clearance during extensive agriculture development.…”
Section: Introductionmentioning
confidence: 99%
“…During the same dry years the phenomenon know as "Sahelian paradox" (Descroix et al, 2009) was observed in many part of the Sahel: an increase in runoff despite the deficit in rainfall (Albergel, 1987;Amani and Nguetora, 2002;MahĂ© et al, 2003MahĂ© et al, , 2005MahĂ© and Paturel, 2009). This phenomenon resulted from a discharge increase in exorheic 1 basins (Amani and Nguetora, 2002;MahĂ© et al, 2003MahĂ© et al, , 2005MahĂ© and Paturel, 2009;Descroix et al, 2009;Amogu et al, 2010) and in larger pond surfaces, infiltration and water table levels in the endorheic 2 areas (Desconnet et al, 1997;Leduc et al, 2001;Gardelle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of our statistical model imply a non-trivial amount of unexplained variation, Gardelle et al (2010) reported similar performance (R 2 = 0.78) for a model relating precipitation and water extent in a single lake, and noted that the correlation was valid only for a 9-year subset of the 5-decade study period. The sources of uncertainty include the complex hydrological processes that relate precipitation, streamflow, and tank water storage, as well as the nonlinear and heterogeneous relationship between water extent and water storage, the neglect of pre-monsoon tank water extent in the model, and the non-stationary behavior of dry-season losses in the two northernmost watersheds.…”
Section: Assessing the Classification And Model Uncertaintymentioning
confidence: 78%
“…For instance, in situ measurements of tank water storage have been successfully used to calibrate and validate hydrological models in Andhra Pradesh (Perrin et al, 2012) and Tamil Nadu (Van Meter et al, 2016). Other studies in southern India (Mialhe et al, 2008), the USA (Halabisky et al, 2016), Africa (Meigh, 1995;Liebe et al, 2005;Sawunyama et al, 2006;Liebe et al, 2009;Gardelle et al, 2010), and South America (Rodrigues et al, 2012) also use surface water bodies as aggregators of streamflow.…”
mentioning
confidence: 99%